Role ambiguity and its relationship to psychological pressures among school counselors in the cities of Mecca and Jeddah - Munshi, Jehad Suliman (Journal of Educational and Psychological Sciences, 2020)
The current study aimed to identify the role ambiguity and its relation to the psychological pressures among school counselors in the cities of Makkah and Jeddah. In order to achieve the objectives of the study, the descriptive method was used. The sample was chosen randomly among the school counselors in Makkah and Jeddah (100 school counselors). The study used two measures to obtain the results (The preparation of the ambiguity of the role (preparation of Jumaili and Bijari, 2008) and the measure of chronic psychological stress (the preparation of Schultz and Baker and the translation by Kalioubi and Tangor, 2014), the results of the search found that:-There is a statistically significant relationship between the role ambiguity and psychological pressure in the research sample-There were no statistically significant differences between the school counselors on the role ambiguity due to the specialization-There were statistically significant differences between the school counselors on the role ambiguity according to the experience The differences were for the benefit of the less experience.-There were statistically significant differences between the specialized and non-specialist school counselors in the level of psychological pressure. The differences were for the benefit of the non-specialist study sample-There are statistically significant differences in the level of psychological pressure according to the experience of the school counselors and The differences were for the benefit of the less experience.
Keywords: Role ambiguity; psychological pressure; student counselors